AI-DRIVEN TRANSFORMATION: A TECHNICAL ANALYSIS OF MODERN SUPPLY CHAIN OPERATIONS - Viswaprakash Yammanur (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This comprehensive article explores the transformative impact of artificial intelligence on modern supply chain operations, examining the integration of advanced technologies across manufacturing sectors. The article investigates key technological frameworks, implementation methodologies, performance metrics, and environmental considerations in AI-driven manufacturing systems. The article encompasses demand forecasting architectures, logistics optimization, manufacturing integration, data architecture, and security considerations. Through extensive analysis of manufacturing facilities worldwide, the article demonstrates significant improvements in operational efficiency, cost reduction, and sustainability metrics. The article reveals how AI integration has revolutionized traditional manufacturing processes through enhanced prediction capabilities, optimized resource utilization, and improved environmental compliance, while addressing crucial challenges in data quality, model maintenance, and system scalability.